2020
DOI: 10.1200/edbk_279505
|View full text |Cite
|
Sign up to set email alerts
|

Toward Modernization of Geriatric Oncology by Digital Health Technologies

Abstract: The number of older adults with cancer is increasing. Over the past 3 decades, geriatric oncology research has focused on improving the assessment of frailty and fitness of older adults with cancer as well as methods of improving their outcomes. At the same time, advances in digital health technologies have opened new frontiers for reaching this goal. Digital health technologies encompass a variety of solutions, from electronic patient-reported outcomes (ePROs) to big data and wireless sensors. These solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For geriatric oncology, contexts of use might include baseline frailty or electronic rapid fitness assessments and monitoring for adverse events or functional deterioration between clinic visits. The use of home-based electronic patient-reported outcomes monitoring is currently being evaluated for the latter purpose [ 39 ].…”
Section: Target Digital Innovation To Do the Greatest Good For Indivi...mentioning
confidence: 99%
“…For geriatric oncology, contexts of use might include baseline frailty or electronic rapid fitness assessments and monitoring for adverse events or functional deterioration between clinic visits. The use of home-based electronic patient-reported outcomes monitoring is currently being evaluated for the latter purpose [ 39 ].…”
Section: Target Digital Innovation To Do the Greatest Good For Indivi...mentioning
confidence: 99%
“…Although the familiarity of older adults with technology is increasing, barriers to wider adoption include very old age, lower disposable income, and higher co‐morbidity. 139 , 140 , 141 Although patients with cognitive impairment and high degree of frailty are probably less likely to direct benefit from DH approaches to disease management and care, DH technology may provide support to their caregivers. Whilst it has been shown that older adults are less likely to use new technology compared with younger adults, there is ample evidence that they also desire interaction with new technologies to remain active and engaged with society.…”
Section: Limitations Faced By Older Adults In Using Digital Health Te...mentioning
confidence: 99%
“…Although the familiarity of older adults with technology is increasing, barriers to wider adoption include very old age, lower disposable income, and higher co‐morbidity 139–141 . Although patients with cognitive impairment and high degree of frailty are probably less likely to direct benefit from DH approaches to disease management and care, DH technology may provide support to their caregivers.…”
Section: Limitations Faced By Older Adults In Using Digital Health Te...mentioning
confidence: 99%
“…As cancer remains a significant disease affecting the geriatric population, it is necessary to consider the relevant applications and ease of use [ 12 , 13 ]. Less than half of adults over the age of 65 years reported owning a smartphone in 2017, with an increase of 24% from 2013.…”
Section: Impact On Oncology Carementioning
confidence: 99%